Analisis Kontrastif Sintaksis Penggunaan Gerund dalam Bahasa Inggris dan Bahasa Arab - Siti Masrifah Nur Aini; Zulfa Nur Ikhwan; Muhammad Alfan (Lisanan Arabiya: Jurnal Pendidikan Bahasa Arab, 2021)
The use of the gerund in English grammar and Arabic in the realm of syntax is a basic discussion as provisions for language learners. Syntax contrastive analysis of using mashdar and gerund can make it easier for someone to understand the use of mashdar easily. This view is the background of this research. The purpose of this study was to analyze the equations and use of mashdar and gerund from a syntactic aspect. This type of research is literature review (library research) where the approach uses qualitative methods that are descriptive analysis to process data. In this study, the authors used several methods, namely data methods and data analysis using language contrastive analysis methods in English and Arabicgrammar books. Similarities between gerund and masdar such as gerund and masdar can be the subject of a nominal sentence (mubtada'), a subject of a verbal sentence (fa' il), a nominal predicate (khabar), a verb object (maf'u l bih), a modifier noun (mudaf ilaih), lies the adverb of time (Zaraf zaman), falls after the question word (istifham), falls after the demonstrative (isim isyarah). Whereas the difference is that there is masdar muawwal, masdar becomes taukid, masdar explores a job, masdar describes the type of work, masdar is a description of the type of fi'il or its nature, masdar becomes a trait, gerund becomes short anition, gerund becomes adjective, gerund fell after the possessive adjective.